39.1k views
4 votes
Solve the given system by substitution.

Solve the given system by substitution.-example-1
User Mtk
by
6.4k points

2 Answers

2 votes
g= 2h-3
Substitute the value of (g) 4g-5h=-6

4(2h-3) - 5h = -6
8h - 12 - 5h = -6
Now -12 is going other side and it’ll change sign
3h= -6+12
3h = 6
H= 6/3
H= 2



CheckBy substitute the value of h
g= 2h - 3
g = 2(2) - 3
g= 4-3
g = 1

1g = 1
Hence proved.
User PushNpop
by
5.8k points
0 votes

Answer:

G = 1

h = 2

Explanation:

4(2h - 3) - 5h = -6

8h - 12 - 5h = -6

3h - 12 = -6

3h = 6

h = 2

g = 2(2) - 3

g = 4 - 3

g = 1

User Vyas Reddy
by
5.3k points